2018
DOI: 10.1097/md.0000000000011629
|View full text |Cite
|
Sign up to set email alerts
|

Remote intervention using smartphone for rural women suffering from premenstrual syndrome

Abstract: Timely treatment of premenstrual syndrome (PMS) is not always available for rural women, because the local medical resources are insufficient. The efficacy of remote intervention by smartphone on PMS has not been confirmed.A retrospective analysis was performed on rural PMS patients between January 2014 and December 2015. After a propensity score matched analysis, 60 patients were enrolled and evenly divided into remote group and outpatient group. Multidisciplinary therapy including cognitive-behavioral therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This data is in line with our main hypothesis concerning the workability of online training to improve the well-being of women, despite the fact that it is limited to physical activity. In a previous retrospective study, online training had been found to be just as effective as face-to-face [ 28 ]. However, a multidisciplinary approach was used, so no clear connections between physical activity and improving the symptoms could be shown.…”
Section: Discussionmentioning
confidence: 99%
“…This data is in line with our main hypothesis concerning the workability of online training to improve the well-being of women, despite the fact that it is limited to physical activity. In a previous retrospective study, online training had been found to be just as effective as face-to-face [ 28 ]. However, a multidisciplinary approach was used, so no clear connections between physical activity and improving the symptoms could be shown.…”
Section: Discussionmentioning
confidence: 99%
“…First, in previous studies, the target group of healthcare providers was not taken into consideration. Previous studies have shown positive results regarding the effect of online CBT interventions for reducing functional and psychological dysfunction caused by PMS, its impact on daily life, the severity of symptoms, and the related disability in different groups including urban women [ 49 ], rural women [ 50 ], and students [ 51 , 52 ]. However, according to the research group, most studies were not theory-based and did not use behavior modification techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The role of genetic factors in the predisposition to PMS has been an active and interesting area for many researchers yet definitive conclusions have not emerged. Some studies suggest a possible association with estrogen receptor alpha (ESR1) gene (13)(14)(15). In one report, cells from women with and without PMS appeared to show different response patterns to the components of the ESC/E (Z) complex containing the ESR1 gene.…”
Section: Risk Factor Of Pmsmentioning
confidence: 99%